Camp average - Battle, Craig, 1980- (Owlkids Books, 2019)
Eleven-year-old Mack and his friends have loved their time at Camp "Average," as they call it, since their summer sports teams never win anything and they can just have fun on their own terms all summer. So, when the "winner" Winston takes over as camp director and eliminates all non-competitive activities, including Mack's favorite water events, Mack and his friends have to find a way to lose so badly that Winston the winner gives up and things get back to normal.